Increasing SERCA function promotes initiation of calcium sparks and breakup of calcium waves - Sato, Daisuke (J Physiol, 2021)
Waves of sarcoplasmic reticulum (SR) calcium (Ca) release can cause arrhythmogenic afterdepolarizations in cardiac myocytes. Ca waves propagate when Ca sparks at one Ca release unit (CRUs) recruit new Ca sparks at neighboring CRUs. Under normal conditions, Ca sparks are too small to recruit neighboring Ca sparks where Ca sensitivity is also low. However, under pathological conditions such as a Ca overload or ryanodine receptor (RyR) sensitization, Ca sparks can be larger and propagate more readily as macro-sparks or full Ca waves. Increasing SERCA pump activity promotes SR Ca load, which promotes RyR opening and increases driving force of the Ca release flux from SR to cytosol, promoting Ca waves. However, high SERCA activity can also decrease local cytosolic [Ca] as it approaches the next CRU, thereby reducing wave appearance and propagation. In this study, we use a physiologically detailed model of subcellular Ca cycling and experiments in phospholamban-knockout mice, to show how Ca waves are initiated and propagate and how different conditions contribute to the generation and propagation of Ca waves. We show that reducing diffusive coupling between Ca sparks by increasing SERCA activity prevents Ca waves by reducing [Ca] at the next CRU, as do Ca buffers, low intra-SR Ca diffusion, and distance between CRUs. Increasing SR Ca uptake rate has a biphasic effect on Ca wave propagation, initially it enhances Ca spark probability and amplitude and CRU-coupling, thereby promoting arrhythmogenic Ca waves propagation, but at higher levels SR Ca uptake can abort those arrhythmogenic Ca waves.